2006
DOI: 10.1002/jrs.1566
|View full text |Cite
|
Sign up to set email alerts
|

Phonon confinement studies in nanocrystalline anatase‐TiO2 thin films by micro Raman spectroscopy

Abstract: Raman studies were performed on titania thin films prepared by polyethylene glycol (PEG) assisted, low-temperature, sol-gel method. The Raman spectra of the films show a systematic blue shift in the peak position and a broadening in the full width at half-maximum (FWHM) when compared with those of the bulk anatase TiO 2 powder. Several reports have appeared indicating this kind of peak shift and broadening of FWHM, which were attributed to the confinement of phonons in the anatase nanocrystallites. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
144
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(171 citation statements)
references
References 37 publications
17
144
1
5
Order By: Relevance
“…These observations are in line with models that indicate phonon confinement by a decrease of the effective particle size. In fact, if various models for phonon confinement [33][34][35] (see SI) are applied to the shifts in peak position and the changes in the FWHM at the Eg peak, the corresponding length scale results as ~10-20 nm -this well in line with direct observation of voids in the TEM walls with spacings at ≈ 20 nm (Fig. 2h).…”
supporting
confidence: 77%
“…These observations are in line with models that indicate phonon confinement by a decrease of the effective particle size. In fact, if various models for phonon confinement [33][34][35] (see SI) are applied to the shifts in peak position and the changes in the FWHM at the Eg peak, the corresponding length scale results as ~10-20 nm -this well in line with direct observation of voids in the TEM walls with spacings at ≈ 20 nm (Fig. 2h).…”
supporting
confidence: 77%
“…This implies that even though peak positions in these samples are characteristic to crystalline rutile formation there is no long range ordering in these samples and the Raman shifts are most likely represented by amorphous vibrations. It has been suggested that peak broadening occurs due to nanocrystallinity and quantum confinement effects, and that there is a characteristic dependency between grain size and peak position and broadening in Raman analysis [23,[25][26][27]. Finally Li Bassi et al [22] pointed out that materials with smaller particles (~4.4 nm) have Raman spectrum similar to that of amorphous materials, which could also be the case here.…”
Section: Resultsmentioning
confidence: 67%
“…In addition, in the Raman spectrum of the WO 3 -TiO 2 composite film annealed at 600°C (Fig. 1C), the mode emerging at 151.5 cm -1 is due to the crystallization of the TiO 2 in the anatase form [45]. Also, the anatase main band is high-frequency shifted (151.5 cm -1 ) with respect to the value of commercial anatase TiO 2 powder (142.5 cm -1 ), indicating that the TiO 2 is constituted of TiO 2 nanoparticles.…”
Section: Characterizationmentioning
confidence: 98%
“…Also, the anatase main band is high-frequency shifted (151.5 cm -1 ) with respect to the value of commercial anatase TiO 2 powder (142.5 cm -1 ), indicating that the TiO 2 is constituted of TiO 2 nanoparticles. A phonon confinement model has been applied to establish a relation between the crystallite sizes and the main Raman peak position of TiO 2 , and the observed shift corresponds to a crystallite size of *5 nm [45]. Compared with the WO 3 sample annealed at 500°C, which had amorphous TiO 2 , formation of the orthorhombic phase of WO 3 in the WO 3 -TiO 2 composite film heat treated at 600°C has been favored by the presence of crystalline anatase.…”
Section: Characterizationmentioning
confidence: 99%